Butanediols production from erythritol on Rh promoted catalyst - Virgilio, Emanuel Martin (2020)
The C-O hydrogenolysis of Erythritol to Butanodiols was studied in aqueous solution at 473 K and 25 bar of H2 using Rh/ReOx/TiO2 and the monometallic Rh/TiO2 and ReOx/TiO2 catalysts. The solids were characterized by temperature programmed reduc-tion (TPR), TEM and XPS. TPR and XPS showed that ReOx species are close to Rh particles leading to reduction at lower temperature than Re on mono-metallic catalyst. However, some segregated Rhenium species were suspected by TPR profile for the bimetallic catalyst and detected by TEM. Re/TiO2 exhibited low activity forming only products from dehydration and epimerization. Although Rh/TiO2 showed high activity (total conversion at 14 h), was more selective to C-C cleavage leading to lower car-bon products. Rh/ReOx/TiO2, showed instead, a good activity and selectivity towards C-O hydrogenolysis route yielding 37.5% of Butanodiols. Activation en-ergy and reaction orders on ERY (0.58) and H2 (0.53) were estimated from experiences made at dif-ferent reaction conditions.